2019
DOI: 10.1186/s12913-019-4327-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinician dashboard views and improvement in preventative health outcome measures: a retrospective analysis

Abstract: Background Measuring and reporting outcome data is fundamental for health care systems to drive improvement. Our electronic health record built a dashboard that allows each primary care provider (PCP) to view real-time population health quality data of their patient panel and use that information to identify care gaps. We hypothesized that the number of dashboard views would be positively associated with clinical quality improvement. Methods We performed a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 9 publications
0
25
0
1
Order By: Relevance
“…[32][33][34] Guideline dissemination methods have varying effectiveness and many lead to only modest or even no impact on changing practice. [35][36][37][38] While incorporation in the EHR has been considered a potential implementation strategy, findings from studies have been mixed. 37,[39][40][41][42] The Duke Health simple implementation strategy using Health Maintenance combined with tailored laboratory results with follow-up recommendations resulted in substantially improved algorithm-based screening while reducing practice variation.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Guideline dissemination methods have varying effectiveness and many lead to only modest or even no impact on changing practice. [35][36][37][38] While incorporation in the EHR has been considered a potential implementation strategy, findings from studies have been mixed. 37,[39][40][41][42] The Duke Health simple implementation strategy using Health Maintenance combined with tailored laboratory results with follow-up recommendations resulted in substantially improved algorithm-based screening while reducing practice variation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, during development, general guidelines for healthcare dashboard design were considered, such as easy-to-read, graphical displays and system connectivity and integration [4,14]. The provided dashboard differs in terms of its absence of focus on individual patients and their treatments, compared to more common conditions that do not belong to the group of rare diseases (comparable examples [12,13]). This supports the statement by KHARATI ET AL.…”
Section: Lessons Learnedmentioning
confidence: 99%
“… 4 Other studies found no significant impact on outcomes; for example, in one study, no significant association between dashboard use and preventive screening quality scores was identified. 5 Importantly, much of the work in this literature involves case studies of single dashboards or review articles. These studies have generated important insights regarding development and implementation of dashboards in specific cases, but few comparative studies that contrast multiple dashboards across different institutions have been done.…”
Section: Introductionmentioning
confidence: 99%